Can Europe recover without credit? - Zsolt Darvas (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
Data from 135 countries covering five decades suggests that creditless recoveries, in which the stock of real credit does not return to the pre-crisis level for three years after the GDP trough, are not rare and are characterised by remarkable real GDP growth rates: 4.7 percent per year in middle-income countries and 3.2 percent per year in high-income countries. However, the implications of these historical episodes for the current European situation are limited, for two main reasons. First, creditless recoveries are much less common in high-income countries, than in low-income countries which are financially undeveloped. European economies heavily depend on bank loans and research suggests that loan supply played a major role in the recent weak credit performance of Europe. There are reasons to believe that, despite various efforts, normal lending has not yet been restored. Limited loan supply could be disruptive for the European economic recovery and there has been only a minor substitution of bank loans with debt securities. Second, creditless recoveries were associated with significant real exchange rate depreciation, which has hardly occurred so far in most of Europe. This stylised fact suggests that it might be difficult to re-establish economic growth in the absence of sizeable real exchange rate depreciation, if credit growth does not return.
Keywords: E32; E44; E51; F31; G21; O40; 330; creditless recoveries; credit growth; financial structure; real exchange rate adjustment; Kreditmarkt; Konjunktur; Kaufkraftparität; Bruttoinlandsprodukt; Europa